A giant and extensive solitary Peutz–Jeghers-type polyp in the antrum of stomach: Case report. Issue 49 (December 2017) - Zou, Bai-Cang; Wang, Feng-Fan; Zhao, Gang; Lu, Xiao-Lan; Zhang, Li; Zhao, Ping; Shi, Hai-Tao; Qin, Bin; Guo, Xiao-Dan; Zhang, Jing
Abstract: Rationale: A solitary Peutz–Jeghers-type polyp is a hamartomatous polyp which without either mucocutaneous pigmentation or a family history of Peutz–Jeghers syndrome (PJS). It can occur in all of the gastrointestinal tract, but it is extremely rare in the stomach. Patient concerns: A 53-year-old man was admitted to the local hospital with left upper abdominal pain lasting 2 weeks. A gastroscopy showed a giant and extensive bulging lesion on the greater curvature and posterior and anterior walls of the gastric antrum, involving three-quarters of the gastric wall. Endoscopic ultrasonography showed a muscularis mucosa lesion. Diagnoses: A solitary Peutz–Jeghers-type polyp in the antrum of stomach. Interventions: The patient underwent an endoscopic submucosal dissection (ESD). Outcomes: The patient recovered quickly, without any complications. Lessons: This is the second largest gastric solitary Peutz–Jeghers-polyp reported until now, and the largest gastric solitary Peutz–Jeghers type-polyp treated by endoscope.